Profile of Communication Skills of Students in Groups with the Application of Blended Learning using Project-Based Learning Model - Widi Purwianingsih; Dhiya Ananda Lestari; Taufik Rahman (Universitas Pendidikan Indonesia (UPI), 2023)
Communication is one of the important 21st-century skills provided to students. In Indonesia, communication skills in education are still considered less trained, especially in the conditions of the past Covid-19 pandemic. Learning using blended learning is one way that can be used to provide this skill, especially in the transition conditions from online to offline learning as it is today. This study aims to analyze the profile of communication skills of high school students using the blended learning model Project Based Learning (PjBL) on ecological concepts. The study also analyzed the results of projects that students have worked on during learning. This study uses the descriptive method. The study was conducted on 31 students in one class X science from one of the private high schools in the city of Bandung using the purposive sampling method. Data was collected with non-test instruments in the form of observation sheets and project assessments. Verbal communication is measured through observation sheets at the time of presentation of the project work. The ability of written communication is based on assessment in media and technology. Results showed that the average student's verbal communication skills were 86% (very high category), and the average written communication score was 85% (high category). The product results from the project show an average value of 74% (high category). All students are generally interested in blended learning using the PjBL model.